Упростите выражение: [latex]1-\frac{a^{3}-b^{3}}{(a^{2}-b^{2})(a+b)}[/latex] Решите уравнение: [latex]\frac{x+2}{2-x}=2[/latex]

Упростите выражение: [latex]1-\frac{a^{3}-b^{3}}{(a^{2}-b^{2})(a+b)}[/latex] Решите уравнение: [latex]\frac{x+2}{2-x}=2[/latex]
Гость
Ответ(ы) на вопрос:
Гость
1)  [latex]1-\frac{a^{3}-b^{3}}{(a^{2}-b^{2})(a+b)}[/latex] [latex]1-\frac{(a^{2}+ab+b^{2})(a-b)}{(a-b)(a+b)(a+b)}[/latex]     [latex]1-\frac{a^{2}+ab+b^{2}}{(a+b)^{2}}[/latex] [latex]\frac{a^{2}+2ab+b^{2} - a^{2}-ab-b^{2}}{(a+b)^{2}}[/latex]  [latex]\frac{ab}{(a+b)^{2}}[/latex]        2) [latex]\frac{x+2}{2-x}=2 [/latex] домножаем на 2-x, учитывая, что x не может быть равен 2 x+2 = 2(2-x) x+2 = 4-2x 3x = 2 x=2/3                                  
Не нашли ответ?
Ответить на вопрос
Похожие вопросы